How International Treaties Binding for Domestic Law? A Book Review “Treaties Under Indonesian Law: A Comparative Study” Dr. iur. Damos Dumoli Agusman, PT Remaja Rosda Karya, Bandung, 2014, ISBN 978-979-692-597-1, 554 Pages - Priyambodo, Muhammad (Universitas Negeri Semarang, 2022)
International treaties have unique characteristics, especially when faced with the question of how an international treaty applies in a country. The book